Language, the social mirror - Chaika, Elaine 1934- (Rowley, Mass. Newbury House Publishers, 1982)
Discusses the ways people use language in society with chapters on kinesics, dialect, and bilingualism.
Includes index.
Bibliography: p. 247-254.
Library's copy is a photocopy.
Keywords: Language and languages; Linguistics; Language and languages; Linguistics